Resolution, structures, and vibrational circular dichroism of helicoidal trinickel and tricobalt paddlewheel complexes. Issue 6 (13th March 2020) - Cortijo, Miguel; Valentín‐Pérez, Ángela; Rosa, Patrick; Daugey, Nicolas; Buffeteau, Thierry; Hillard, Elizabeth A.
Abstract: It has been recently shown that enantiomers of the helicoidal paddlewheel complex [Co3 (dpa)4 (CH3 CN)2 ] 2+ (dpa = the anion of 2, 2′‐dipyridylamine) can be resolved using the chiral [As2 (tartrate)2 ] 2− anion (AsT) and that these complexes demonstrate a strong chiroptical response in the ultraviolet‐visible and X‐ray energy regions. Here we report that the nickel congener, [Ni3 (dpa)4 (CH3 CN)2 ] 2+, can likewise be resolved using AsT. Depending on the stereochemistry of the enantiopure AsT anion, one or the other of the trinickel enantiomers crystallize from CH3 CN and diethyl ether in space group P 421 2 as the (NBu4 )2 [Ni3 (dpa)4 (CH3 CN)2 ](AsT)2 ·[solvent] salt. After resolution, the AsT salts were converted into the PF6 − salts by anion exchange, with retention of the chirality of the trinickel complex. The enantiopure [Ni3 (dpa)4 (CH3 CN)2 ](PF6 )2 ·2CH3 CN and [Co3 (dpa)4 (CH3 CN)2 ](PF6 )2 ·CH3 CN·C4 H10 O compounds crystallize in space groups C 2 and P 21, respectively. Both the Ni(II) and Co(II) complex cations are stable towards racemization in CH3 CN. Vibrational circular dichroism (VCD) data obtained in CD3 CN demonstrate the expected mirror image spectra for the enantiomers, the observed peaks arising from the dpa ligand. The VCD response is significant, with Δε values up to 6 Lmol −1 cm −1 and vibrational dissymmetry factors on the order of 10 −3 . Density functional theory calculations well reproduce the experimental spectra, showing little difference between the peak position, sign, and intensity in the VCD for the cobalt and nickel complexes. These results suggest that VCD enhancement of these peaks is unlikely, and their remarkable intensity may be due to their rigid helicoidal structure. Abstract :